(untitled) (UNIZIK Journal of Marketing, 2025)
This study examined the impact of digitalization on the performance of commercial banks in Nigeria using panel data from 2012 to 2022. The research adopted an ex post facto and quantitative research involving secondary form of data. It focused on how mobile banking, total assets, and non-performing loans influence return on assets (ROA). Employing descriptive statistic, panel least square, cross-sectional dependent test, fixed and random effects models, the findings indicate that digitalization generally enhances bank performance. However, results vary depending on scale and infrastructure costs. Mobile banking initially shows a positive effect on ROA, but fixed effects suggest a slight negative impact possibly due to cost implications. Total assets also exhibit mixed outcomes. The study underscores the need for strategic digital adoption that balances efficiency with cost management. Key recommendations include investment in secure digital infrastructure, continuous staff training, and increased public awareness on data protection to sustain profitability and customer trust.